Prediction of the lignocellulosic winery wastes behavior during gasification process in fluidized bed: Experimental and theoretical study - Rodriguez, Rosa Ana (2018)
This work presents studies about the gasification of the lignocellulosic winery wastes in fluidized bed to obtain energy. Based on the exergy analysis, the exergetic improvement potential (IP) and sustainability index (SI) variations with different operational variables were analyzed. IP increases and SI decreases when moisture content, ER and SBR augment. On the other hand, both indexes present contrary behavior with the temperature increasing. Additionally, the kinetic behavior was investigated using a macro thermo-balance. The thermal decomposition of the studied biomass wastes at three heating rate, 5, 10 and 15 °C/min under steam/air mixture atmosphere show that the gasification takes place in three visible stage: water vaporization, pyrolysis and the last step associated with the reaction of the char by CO 2 . The distributed activation energy model method (DAEM) was used. The decomposition is not a single reaction stage, it includes the contributions of parallel reaction steps on the global reaction rate. Last, the fluidization was analyzed using air at room temperature and local atmospheric pressure. Each experiment was carried out with 100% and 75% v lignocellulosic wastes. Segregation, slugging and channelization in all studied cases. However, the addition of sand particles improves the behavior of both winery wastes.